38 KRUPPEL-LIKE FACTOR 15 IS A NOVEL REGULATOR OF CARDIOMYOCYTE HYPERTROPHY. (1st March 2007) - Fisch, S.; Gray, S.; Heymans, S.; Haldar, S.; Wang, B.; Zhu, Y.; Liao, R.; Pinto, Y. M.; Jain, M. K.
Abstract : Cardiac hypertrophy is a common response to injury and hemodynamic stress and an important harbinger of heart failure and death. Herein we identify Kruppel-like factor 15 (KLF15) as a novel inhibitor of cardiac hypertrophy. Myocardial expression of KLF15 is reduced in rodent models of hypertrophy and in biopsy samples from patients with pressure overload induced by chronic valvular aortic stenosis. Overexpression of KLF15 in neonatal rat ventricular cardiomyocytes inhibits cell size, protein synthesis, and hypertrophic gene expression. KLF15-null mice are viable but, in response to pressure overload, develop an eccentric form of cardiac hypertrophy characterized by increased heart weight, exaggerated expression of hypertrophic genes, left ventricular cavity dilatation with increased myocyte size, and reduced left ventricular systolic function. Mechanistically, a combination of promoter analyses and gel-shift studies suggests that KLF15 can inhibit GATA4 and MEF2 function. These studies identify KLF15 as part of a heretofore unrecognized pathway regulating the cardiac response to hemodynamic stress.